Pengembangan kemampuan guru ekonomi di Kediri melalui kegiatan pelatihan asesmen kompetensi minimum (AKM) - Muhammad Anas; Mochamad Muchson; Sugiono Sugiono; Rr. Forijati (Rengganis Jurnal Pengabdian Masyarakat, 2021)
As one of the components of the national education system, teachers as the spearhead in achieving success in achieving national education goals play a very important role in the implementation of AKM. However, at the operational level of the policy, teachers do not fully understand and have sufficient competence regarding the implementation of AKM. Several problems as identified results show that the economy teachers in the district and city of Kediri: 1) do not understand the concept of AKM, both AKM AN and AKM Class; 2) does not have adequate skills in developing AKM which includes: literacy and numeracy AKM, character survey, and learning environment survey; and 3) do not have sufficient skills in developing HOTS questions for economic lessons. In order to improve the ability of teachers in AKM, training is carried out with the aim of increasing the ability of teachers to: 1) development of AKM materials; 2) development of Class AKM materials; 3) development of character survey instruments; 4) development of learning environment survey instruments; and 5) compilation of HOTS questions. The AKM training methods include: various tutorials / lectures, assignments, discussions, and evaluations. The results of the training show that teachers must have increased competency in the following aspects: AKM knowledge, literacy, numeracy, preparation of article-based AKM questions, and preparation of HOTS questions in economic subjects.